Effects of enhanced cutaneous sensory input on interlimb strength transfer of the wrist extensors. Issue 6 (27th March 2020) - Barss, Trevor S.; Klarner, Taryn; Sun, Yao; Inouye, Kristy; Zehr, E. Paul
Abstract: The relative contribution of cutaneous sensory feedback to interlimb strength transfer remains unexplored. Therefore, this study aimed to determine the relative contribution of cutaneous afferent pathways as a substrate for cross‐education by directly assessing how "enhanced" cutaneous stimulation alters ipsilateral and contralateral strength gains in the forearm. Twenty‐seven right‐handed participants were randomly assigned to 1‐of‐3 training groups and completed 6 sets of 8 repetitions 3x/week for 5 weeks. Voluntary training (TRAIN) included unilateral maximal voluntary contractions (MVCs) of the wrist extensors. Cutaneous stimulation (STIM), a sham training condition, included cutaneous stimulation (2x radiating threshold; 3sec; 50Hz) of the superficial radial (SR) nerve at the wrist. TRAIN + STIM training included MVCs of the wrist extensors with simultaneous SR stimulation. Two pre‐ and one posttraining session assessed the relative increase in force output during MVCs of isometric wrist extension, wrist flexion, and handgrip. Maximal voluntary muscle activation was simultaneously recorded from the flexor and extensor carpi radialis. Cutaneous reflex pathways were evaluated through stimulation of the SR nerve during graded ipsilateral contractions. Results indicate TRAIN increased force output compared with STIM in both trained (85.0 ± 6.2 Nm vs. 59.8 ± 6.1 Nm) and untrained wrist extensors (73.9 ± 3.5 Nm vs. 58.8 Nm). Providing 'enhanced' sensory input during training (TRAIN + STIM) also led to increases in strength in the trained limb compared with STIM (79.3 ± 6.3 Nm vs. 59.8 ± 6.1 Nm). However, in the untrained limb no difference occurred between TRAIN + STIM and STIM (63.0 ± 3.7 Nm vs. 58.8 Nm). This suggests when 'enhanced' input was provided independent of timing with active muscle contraction, interlimb strength transfer to the untrained wrist extensors was blocked. This indicates that the sensory volley may have interfered with the integration of appropriate sensorimotor cues required to facilitate an interlimb transfer, highlighting the importance of appropriately timed cutaneous feedback. Abstract : No study has directly assessed the relative contribution of somatosensory feedback to interlimb strength transfer. Providing 'enhanced' cutaneous input during unilateral wrist extension training blocked the interlimb strength transfer to the untrained limb that was seen when participants trained with voluntary contractions only. This study highlights the importance of appropriate cutaneous sensory feedback to the interlimb transfer of strength following unilateral training.